Use Of Multimedia Technologies in Primary Class Mathematics Lessons - Otojanova N.B; Pardaboyeva M.U. (Genius Journals, 2024)
Today, the only and most modern form of information presentation is multimedia tools. This article shows how multimedia tools can be used in primary classes
Keywords: Information technologies; multimedia; information systems